PERANAN MODAL SOSIAL PADA MGMP PPKn DALAM MEMBENTUK KOMPETENSI GURU DI KOTA PEKANBARU - Ahmad Eddison; Hambali Hambali; Hariyanti Hariyanti (Universitas Sriwijaya, 2021)
ABSTRACTThis paper analyzes social capital as an important factor for teachers who are gathered in the MGMP (Musyawarah Guru Mata Pelajaran) organization in the formation of teacher competencies which include; pedagogic competence, personality competence, social competence and professional competence. The purpose of this study is to analyze; 1) social capital and 2) the role of social capital in MGMP-PPKn SMA to form teacher competence in Pekanbaru City. The subjects in this study were administrators and members of the PPKn MGMP, the determination of research subjects (informants) was carried out by purposive sampling technique. Data collection techniques using interviews, observation and documentation. Data analysis techniques through 1) Data Collection 2) Data Reduction 3) Data display, and 4) Data verification. The findings in this study are that the application of social capital in organizations is carried out with three main elements as pillars of togetherness, namely; 1) trust, 2) norms and 3) network. In this study, it does not claim that educator certificates are proof of teacher competence based on policies/laws. However, to get MGMP members to achieve teacher certificates, the findings of this study are that